Insomnia disorder: clinical and research challenges for the 21st century. (9th April 2021) - Ferini‐Strambi, Luigi; Auer, Reto; Bjorvatn, Bjørn; Castronovo, Vincenza; Franco, Oscar; Gabutti, Luca; Galbiati, Andrea; Hajak, Goeran; Khatami, Ramin; Kitajima, Tsuyoshi; McEvoy, Doug; Nissen, Christoph; et al.
Abstract: Background and purpose: Insomnia is a common and debilitating disorder that is frequently associated with important consequences for physical health and well‐being. Methods: An international expert group considered the current state of knowledge based on the most relevant publications in the previous 5 years, discussed the current challenges in the field of insomnia and identified future priorities. Results: The association of trajectories of insomnia with subsequent quality of life, health and mortality should be investigated in large populations. Prospective health economics studies by separating the costs driven specifically by insomnia and costs attributable to its long‐term effects are needed. Ignoring the heterogeneity of insomnia patients leads to inadequate diagnosis and inefficient treatment. Individualized interventions should be promoted. More data are needed on both the impact of sleep on overnight effects, such as emotion regulation, and the potential compensatory effort to counteract diurnal impairments. Another gap is the definition of neurocognitive deficits in insomnia patients compared to normal subjects after chronic sleep loss. There are also a number of key gaps related to insomnia treatment. Expert guidelines indicate cognitive–behavioural therapy for insomnia as first‐line treatment. They neglect, however, the reality of major healthcare providers. The role of combined therapy, cognitive–behavioural therapy for insomnia plus pharmacological treatment, should be evaluated more extensively. Conclusion: Whilst insomnia disorder might affect large proportions of the population, there are a number of significant gaps in the epidemiological/clinical/research studies carried out to date. In particular, the identification of different insomnia phenotypes could allow more cost‐effective and efficient therapies.